LITERATURE ANALYSIS OF SUKUK RATINGS IN INDONESIA BIBLIOMETRIC APPROACH - Afifa Nurhanifah; Siti Khomsatun (Sean Institute, 2023)
This study aims to analyze the development of research rating on sukuk in Indonesi. This research is a literature review using a systematic bibliometric review approach by analyzing 78 research articles. Research articles used as data research , published either nationally indexed by Sinta or non-Sinta and international Scopus. Data was observed and analyzed using VOSviewer and Microsoft Excel 2019, from the number of citations, authors, keywords to emerging research gaps. The results show that research on sukuk rankings in Indonesia was first in 2009, and developed in 2011. The most cited years were 2013 and 2017, and the results of this study also present research gaps with coverage of keyword areas that can still be developed.